Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/ijms23052468
|View full text |Cite
|
Sign up to set email alerts
|

Bivalent EGFR-Targeting DARPin-MMAE Conjugates

Abstract: Epidermal growth factor receptor (EGFR) is a validated tumor marker overexpressed in various cancers such as squamous cell carcinoma (SSC) of the head and neck and gliomas. We constructed protein-drug conjugates based on the anti-EGFR designed ankyrin repeat protein (DARPin) E01, and compared the bivalent DARPin dimer (DD1) and a DARPin-Fc (DFc) to the monomeric DARPin (DM) and the antibody derived scFv425-Fc (scFvFc) in cell culture and a mouse model. The modular conjugation system, which was successfully app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 74 publications
(99 reference statements)
0
2
0
Order By: Relevance
“…They found that medium-sized conjugates exhibited superior antitumor effects. Furthermore, an additional study on DARPin-drug conjugation specifically investigated on bivalent EGFR-targeting DARPin-MMAE conjugates (DAR 2) and monomeric DARPin-Fc-MMAE conjugates (DAR 4), which effectively killed EGFR-overexpressing A431 cells with sub-nanomolar potency [ 70 ]. Additionally, tumor targeted-DARPin has also been conjugated to anticancer proteins like fragmented human lactoferrin (rtHLF4), Cecropin A (CRPA), Cecropin CMV (CRPC).…”
Section: Based On Single-domain Antibodiesmentioning
confidence: 99%
“…They found that medium-sized conjugates exhibited superior antitumor effects. Furthermore, an additional study on DARPin-drug conjugation specifically investigated on bivalent EGFR-targeting DARPin-MMAE conjugates (DAR 2) and monomeric DARPin-Fc-MMAE conjugates (DAR 4), which effectively killed EGFR-overexpressing A431 cells with sub-nanomolar potency [ 70 ]. Additionally, tumor targeted-DARPin has also been conjugated to anticancer proteins like fragmented human lactoferrin (rtHLF4), Cecropin A (CRPA), Cecropin CMV (CRPC).…”
Section: Based On Single-domain Antibodiesmentioning
confidence: 99%
“…Due to more favorable structural characteristics, ESPs have higher tolerance to pH and temperature changes than mAbs, resulting in better in vitro and in vivo stability of the drug conjugates. Several conjugates of affibody molecules [18,25,26], DARPins [20,[31][32][33] and adnectins [35] with drugs and toxins have been developed and have demonstrated anti-tumor activity in preclinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…The feasibility of using ESPs for tumor-targeted delivery of drugs and toxins has been studied for affibody molecules [18,[25][26][27], DARPins [20,[28][29][30][31][32][33], adnectins [34,35] and anticalins [36]. The HER2-targeting ESPs described in the literature interacts with different epitopes on the receptor; e.g., the HER2-targeting affibody molecules bind to subdomain III, the DARPin 9_29 binds to subdomain I and the DARPin G3 binds to subdomain IV [37].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, affibodies encompass only 13 amino acid positions that differ between binding members and therefore, much of the knowledge to manipulate and functionalize these proteins is known [8,9]. A few examples can be recalled that highlight the importance of affibodies and DARPins in several biomedical applications that include both therapeutics [10][11][12] and imaging agents for tumors [13,14].…”
Section: Of 21mentioning
confidence: 99%